2017
DOI: 10.15446/rsap.v19n3.54226
|View full text |Cite
|
Sign up to set email alerts
|

Calidad de vida relacionada con salud en la población Colombiana: ¿cómo valoran los colombianos su estado de salud?

Abstract: Quality of life related to health in the Colombian population is greater than 80 points on a scale of 1 to 100. Alterations such as angst and depression and the perception of pain were the most frequently reported by Colombians. Poverty and a low level of education are determinants of the perception of Colombians regarding their quality of life related to health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
(18 reference statements)
3
7
0
4
Order By: Relevance
“…Regarding self-reported health status in this study, 78.3% of the population reported that they were in good, very good, or excellent health. In general, these results corroborate the findings from a previous study that also estimated perceived Hrqol in the Colombian adult population (15). However, the authors used the Eq-5d 3 level version by the EuroQol group and found that around 70% of the population reported being "completely healthy" (15).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding self-reported health status in this study, 78.3% of the population reported that they were in good, very good, or excellent health. In general, these results corroborate the findings from a previous study that also estimated perceived Hrqol in the Colombian adult population (15). However, the authors used the Eq-5d 3 level version by the EuroQol group and found that around 70% of the population reported being "completely healthy" (15).…”
Section: Discussionsupporting
confidence: 89%
“…Several authors have reported population estimates of Hrqol in Colombia, but for patient populations affected by or being treated for chronic diseases (9)(10)(11)(12). Few of these studies have reported Hrqol normative data for the general population (13)(14)(15).…”
mentioning
confidence: 99%
“…The participants reported low scores for both physical and mental global health in comparison with normative values for the general population in Colombia, which has been estimated at around 80 on a scale of 0 to 100 using different measurements (Finck et al, 2012;Rojas-Reyes et al, 2017). Bogotá showed better mental HRQoL, in comparison with Medellín, which can be related with a lower intensity in armed conflict in the capital.…”
Section: Discussionmentioning
confidence: 76%
“…Asimismo, se encontró similar afectación en las dimensiones de dolor/malestar (33%) y ansiedad/depresión (28%) en otro estudio con migrantes en Inglaterra (30) . Sin embargo, en un estudio realizado en migrantes rurales mayores (edad promedio de 63 años) en China (31) , así como en estudios poblacionales en Perú (25) , Brasil (32) , Colombia (33) , y Chile (34) , si bien estas dos dimensiones suelen ser las más afectadas, la dimensión de dolor/malestar es más afectada que ansiedad/depresión.…”
Section: Discussionunclassified
“…Un poco más de la mitad de migrantes venezolanos trabaja más de nueve horas diarias, y poco más de un tercio percibe un ingreso económico mensual menor o igual a 500 soles mensuales. Este ingreso es menor a la remuneración mínima vital (cantidad mínima de dinero que se debería recibir por una jornada laboral completa en Perú), que es 930 soles mensuales (36) , y sería insuficiente para satisfacer la canasta básica familiar en el Perú, que se estima en 521 soles por persona (33) . Esto puede deberse a que la mayoría de los migrantes no cuentan con permisos para trabajar en Perú, de manera que se ven forzados a aceptar empleos informales con un ingreso mensual bajo.…”
Section: Discussionunclassified